2014
DOI: 10.18869/acadpub.johe.3.2.88
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting occupational accidents in the construction industry (2009-2013)

Abstract: Received: August 2015, Accepted: September 2015Background: There is a high prevalence of occupational injuries due to accidents in construction industries which affect human health. Therefore, the exploration and analysis of contributing factors of such accidents can lead to their prevention and the reduction of their consequences. This study was conducted with the aim to identify factors related to occupational injuries and the severity of their consequences on large construction sites in Iran. Materials & Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The results from the analysis emphasize the role of the nature of injury in such predictions and classifications, and are in agreement with the previous literature on the significance of the nature of injury in determining the severity of occupational injuries [15,16,[59][60][61][62][63][64]. In general, injuries are divided into three main groups in workers' compensation claims: occupational disease, multiple injuries, and specific injuries.…”
Section: Model Intepretation and Application In Safetysupporting
confidence: 86%
“…The results from the analysis emphasize the role of the nature of injury in such predictions and classifications, and are in agreement with the previous literature on the significance of the nature of injury in determining the severity of occupational injuries [15,16,[59][60][61][62][63][64]. In general, injuries are divided into three main groups in workers' compensation claims: occupational disease, multiple injuries, and specific injuries.…”
Section: Model Intepretation and Application In Safetysupporting
confidence: 86%
“…Additionally, these might be due to the weakness in the diagnosis or some failures in the risk management system in the workplace. In addition to physical harm and labor failure, the accidents could cause capital, equipment, and economic losses [1][2][3]. Several factors contribute to the incidence of occupational accidents, some of which are poor safety and work, size and magnitude of industry, lack of coordination, time pressure, financial and budgetary restraint, lack of data and standard information, poor organizational and nonorganizational communication, workers' poor participation in safety issues, workers' expertise, inadequate training, fatigue and exhaustion, improper equipment selection, improper use or inspection, poor safety management or awareness, and lack of protective equipment [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The univariate analysis results showed that 25 respondents felt that supervision in "X" Project were still lacking (62.5%) and 21 respondents behaved unsafely (50.2%). Study conducted in construction between 2009 and 2013 reveal that training factor, housekeeping, and supervision are still being implemented poorly in construction site (Mohammadfam et al, 2014).…”
Section: Resultsmentioning
confidence: 99%